Polls and Elections: Character and Political Time as Sources of Presidential Greatness. Issue 2 (13th May 2016) - Newman, Brian; Davis, Adrian
Abstract : Presidency scholars have long debated whether a president's personal traits or the historical circumstances of their presidency have a bigger effect on presidential performance. We contribute to this debate by examining whether historical conditions (i.e., Skowronek's conception of political time) and two important personal traits (intellectual brilliance and character) relate to presidents' standing in polls of "presidential greatness." We find that both historical conditions and personal traits significantly predict historical evaluations of presidents. One's place in political time strongly shapes a president's greatness rating. At the same time, within Skowronek's categories, presidents with greater intellectual brilliance and stronger character tend to rank higher.